Modified Method of Chain Substitutions as an Alternative to the Integral Method of Economic Analysis - Yu. V. Kirillov (Финансы: теория и практика, 2024)
The aim is to present the results of the development of a modified method of chain substitutions, which is based on the use of the arithmetic mean sum of the results of the influence of each factor on the indicator of interest, taking into account the priority of each factor in all possible variants. At the same time, from the point of view of accuracy, the results obtained using the modified technique practically do not differ from the results of the integral method, however, they exceed it in terms of using a simpler mathematical apparatus. The relevance of the work is determined by the fact that in modern economic conditions (noticeably increased inflation, problems with energy prices), the issue of applying methods of deterministic factor analysis of expenses and incomes becomes especially significant in order to determine the size of the impact of each factor on a specific economic indicator as accurately as possible. However, the chain substitution method used in the vast majority of cases for deterministic factor analysis is inferior in accuracy to the integral method. The scientific novelty of the work lies in the fact that the author uses strict mathematical proofs of the coincidence of the accuracy of the results of the modified methodology and the integral method for various types of deterministic factor models (additive, multiplicative, multiple), which are supported by real practical calculations. Conclusions: the proposed modified method of chain substitutions, due to its mathematical simplicity and proven accuracy of the results obtained, can be widely used in real practical calculations using methods of economic analysis, especially taking into account the computer implementation of algorithms developed in this technique.